First report of the coffee bean weevil araecerus fasciculatus (De Geer) (Coleoptera Anthribidae) as pest of papaya in the Philippines - Caasi-Lit, Merdelyn T.; Lit, Ireneo L., Jr. (2011)
Araecerus fasciculatus (De Geer) (Coleoptera: Anthribidae), a cosmopolitan pest, especially of stored coffee and cocoa beans, is reported for the first time as a pest of papaya in the Philippines. The weevils were first observed to infest papaya planted outside the greenhouses of the Institute of Plant Breeding, Crop Science Cluster, College of Agriculture, University of the Philippines Los Baños, College, Laguna in 2007. Hence, a survey was conducted from 2007 to 2010 to determine the extent of occurrence of the weevil. The nature of damage on papaya is also described for the first time. The life stages reckoned from field-collected specimens were also studied. The eggs are laid on near-ripe fruits and the developing larvae feed inside the maturing fruits, causing blister-like spots which become cracked wounds and later start to rot and become covered with molds.
Keywords: Coffee bean weevil; Papaya -- Diseases and pests